Influence of social media usage on the communication skills of adolescents in Abuja, Nigeria - Adepapo, Adeyemi; Ekunya, Onyeanula; Liadi, Hakeem Onlaniyi (Universitas Negeri Semarang, 2025)
As social media use increases, its role in adolescent self-expression and communication becomes increasingly significant. This study addresses a gap in the literature by examining social media usage and its relationship with communication skills among adolescents in Nigeria’s Federal Capital Territory. Using a cross-sectional survey design, data were collected from 145 adolescents through questionnaires, with reliability confirmed via test-retest (r = 0.76). Descriptive and inferential statistics revealed that WhatsApp is the most frequently used platform, followed by Facebook and Snapchat. Most participants reported daily use of social media for various purposes. A correlation was found between time spent on social media and self-rated communication skills, though opinions on its impact varied. These findings highlight the complex relationship between social media and adolescent communication, suggesting the need for targeted interventions. The study recommends the development of educational programs to improve adolescents' media literacy and promote healthier social media engagement.